Population structure and transmission dynamics of Plasmodium vivax in the Republic of Korea based on microsatellite DNA analysis. - Moritoshi Iwagami; Megumi Fukumoto; Seung-Young Hwang; So-Hee Kim; Weon-Gyu Kho; Shigeyuki Kano (PLoS Neglected Tropical Diseases, 2012)
BACKGROUND: In order to control malaria, it is important to understand the genetic structure of the parasites in each endemic area. Plasmodium vivax is widely distributed in the tropical to temperate regions of Asia and South America, but effective strategies for its elimination have yet to be designed. In South Korea, for example, indigenous vivax malaria was eliminated by the late 1970s, but re-emerged from 1993. We estimated the population structure and temporal dynamics of transmission of P. vivax in South Korea using microsatellite DNA markers. METHODOLOGY/PRINCIPAL FINDINGS: We analyzed 255 South Korean P. vivax isolates collected from 1994 to 2008, based on 10 highly polymorphic microsatellite DNA loci of the P. vivax genome. Allelic data were obtained for the 87 isolates and their microsatellite haplotypes were determined based on a combination of allelic data of the loci. In total, 40 haplotypes were observed. There were two predominant haplotypes: H16 and H25. H16 was observed in 9 isolates (10%) from 1996 to 2005, and H25 in 27 (31%) from 1995 to 2003. These results suggested that the recombination rate of P. vivax in South Korea, a temperate country, was lower than in tropical areas where identical haplotypes were rarely seen in the following year. Next, we estimated the relationships among the 40 haplotypes by eBURST analysis. Two major groups were found: one composed of 36 isolates (41%) including H25; the other of 20 isolates (23%) including H16. Despite the low recombination rate, other new haplotypes that are genetically distinct from the 2 groups have also been observed since 1997 (H27). CONCLUSIONS/SIGNIFICANCE: These results suggested a continual introduction of P. vivax from other population sources, probably North Korea. Molecular epidemiology using microsatellite DNA of the P. vivax population is effective for assessing the population structure and transmission dynamics of the parasites--information that can assist in the elimination of vivax malaria in endemic areas.